Anies Rasyid Baswedan’s Political Communication in Facing the 2024 Election - Lestanata, Yudhi (Jurnal Ilmiah Peuradeun, 2023)
This study analyzes how Anies Rasyid Baswedan’s political communication is in preparation for the upcoming 2024 elections. In this study, we used a qualitative strategy that incorporated the Qualitative Data Analysis (QDA) Miner methodology into our content, network, and cloud analysis using the Nvivo 12 Plus software. The results of this study indicate that account intensity also describes how Anies Rasyid Baswedan carries out political communication or branding activities. The @aniesbaswedan account has the most significant overall and quarterly tweet intensity, with 79.65% of tweets having a restoration sub-theme. This account also has the highest power for the total number of tweets. The 2024 election subtheme generated 11.43% of tweets; finally, the political subtheme was 9.52%. In analyzing the contents of information dissemination related to Anies Rasyid Baswedan’s political communication, his account has carried out direct outreach regarding politics in the face of the 2024 election. In the end, social media has become a place to share political information about Anies Rasyid Baswedan